Oncologic outcomes of neoadjuvant chemotherapy in patients with micropapillary variant urothelial carcinoma of the bladder - Rahman, Syed N; Lokeshwar, Soum D; Syed, Jamil S; Javier-Desloges, Juan F; Press, Benjamin H; Choksi, Ankur U; Rajwa, Pawel; Pradere, Benjamin; Ploussard, Guillaume; Kim, Joseph W; Monaghan, Thomas F; Renzulli, Joseph R; et al. (Urologic oncology, 2023)
BACKGROUND: There is lack of consensus about the effectiveness of neoadjuvant platinum-based chemotherapy in patients with micropapillary variant urothelial carcinoma (MVUC) prior to radical cystectomy. We studied the association between neoadjuvant chemotherapy (NAC) and pathologic response (PR) among patients with micropapillary versus non-variant bladder urothelial carcinoma (UC). METHODS: We queried the National Cancer Database to identify patients with localized UC and MVUC from 2004 to 2017. We restricted our analysis to patients who underwent radical cystectomy with or without NAC. We compared clinical, demographic, and pathologic characteristics associated with NAC. We used multivariable logistic regression and propensity score matching to examine the association between NAC and the occurrence of a pathologic complete response (pT0) and pathologic lymph node positivity (pN+). Kaplan Meier analyses and Cox proportional hazards models were used to assess overall survival (OS). We performed analyses among subsets of patients with clinical stage II (cT2) disease, as well as the entire cohort (cT2-T4). RESULTS: We identified 18,761 patients, including 18,027 with non-variant UC and 734 patients with MVUC. Multivariable analysis revealed that NAC use was associated with greater odds of pT0 (9.64[7.62-12.82], P<0.001), and the association did not differ significantly between MVUC and non-variant UC. In a propensity matched analysis of patients with MVUC, NAC use was associated with higher odds of pT0 (OR 4.93 [2.43-13.18] P<0.001), lower odds of pN+ (OR 0.52 [0.26-0.92] P=0.047) and pathologic upstaging (OR 0.63 [0.34-0.97] P=0.042) in all stages. Similar findings were observed with cT2 disease. No significant association was seen between NAC and OS with MVUC (HR 0.89 [0.46-1.10] P=0.63), including the subset of patients with cT2 (HR 0.83 [0.49-1.06] P=0.58). CONCLUSIONS: NAC is associated with similar pathologic and nodal responses in patients with localized MVUC and non-variant UC. Improvements in pathologic findings did not translate into OS in this retrospective hospital-based registry study.
Keywords: Neoadjuvant Therapy; adjuvantní chemoterapie; nádory močového měchýře; Chemotherapy, Adjuvant; Urinary Bladder; Carcinoma, Transitional Cell; Cystectomy; Neoplasm Staging; močový měchýř; chemotherapy; karcinom z přechodných buněk; neoadjuvantní terapie; staging nádorů; Retrospective Studies; micropapillary; retrospektivní studie; variant; Urinary Bladder Neoplasms; neoadjuvant; cystektomie; lidé; Humans